PERLINDUNGAN HUKUM BAGI KREDITUR DALAM HAL DEBITOR MENYEWAKAN OBJEK JAMINAN FIDUSIA KEPADA PIHAK KE TIGA (ANALISIS KASUS PUTUSAN MAHKAMAH AGUNG NOMOR 1271 K/PDT/2016) - Delvina Alodia; Endang Pandamdari (Jurnal Hukum Adigama, 2018)
Fiduciaire Eigendomsoverdracht or as otherwise known as Fiduciary Transfer of Ownership or Fiduciary Security, is a type of security that has now been used by many people and cannot be denied its importance in the world of private law. In Fiduciary Security, the objects will which remain in control of the person or entity which provides a fiduciary security over the objects (Fiduciary Provider). That is why this security is used to give the fiduciary beneficiary a form of legal certainty and to secure repayment of certain debt. But in reality, there are still many problems concerning this such as the fiduciary beneficiary who doesn’t register the object at the Fiduciary Registration Office, the fiduciary provider doesn’t pay their debts or they may have rented or possibly sold the objects. In this situation, the fiduciary beneficiary faces an immense loss. This journal focuses on the problem where the fiduciary provider has rented the object to another party without the fiduciary beneficiary’s knowledge and what legal protection does the fiduciary beneficiary has concerning this situation. The research method this journal uses is a normative method with the usage of secondary data and qualitative analization. The results of this research is to give a picture of the preventive and repressive legal protection for the fiduciary beneficiary in regards to the fiduciary provider having sold the object without the fiduciary beneficiary’s knowledge.